Characterization of a membrane-associated cytidine diphosphate-diacylglycerol-dependent phosphatidylserine synthase in bacilli. - Dutt, A (1981)
The synthesis of phosphatidylserine in two gram-positive aerobic bacteria has been partially characterized. We have located a cytidine 5'-diphospho-diacylglycerol:L-serine O-phosphatidyltransferase (phosphatidylserine synthase) activity in the membrane fraction of Bacillus licheniformis and Bacillus subtilis. The activity was demonstrated to be membrane associated by differential centrifugation, sucrose gradient centrifugation, and detergent solubilization. The direct involvement of cytidine 5'-diphospho-diacylglycerol in the reaction was demonstrated by the conversion of the liponucleotide phosphatidyl moiety to phosphatidylserine. This activity is dependent on divalent metal ion (manganese being optimal) and is stimulated by nonionic detergent and its product phosphatidylserine. Based on studies with various combinations of products and substrates, the reaction appears to follow a sequential BiBi kinetic mechanism.